(untitled) (Konferensiyalar | Conferences, 2024)
This article examines the importance of self-study and its impact on student development. The article provides a brief description of the topics and main aspects considered within this discipline. This article emphasized that learning depends not only on teachers, but also on the student himself, his motivation, self-study and ability to learn independently. This article examines methods and strategies for independent study, as well as its positive effects on student development, communication, critical thinking, and self-esteem. As a result of learning this method, students understand the importance of independent action in the learning process and apply appropriate strategies to achieve success in their educational activities.